1996
DOI: 10.1113/jphysiol.1996.sp021706
|View full text |Cite
|
Sign up to set email alerts
|

Changes in maximal voluntary force of human adductor pollicis muscle during the menstrual cycle.

Abstract: 1. Muscle strength of the adductor pollicis (AP) was studied throughout the menstrual cycle to determine whether any variation in force is similar to the known cyclical changes in ovarian hormones. Three groups of young women were studied: trained regularly menstruating athletes (trained), untrained regularly menstruating (untrained) and trained oral contraceptive pill users (OCU). In addition a group of untrained young men was studied as controls. 2. Maximum voluntary force (MVF) of AP was measured over a max… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

16
161
3
2

Year Published

2000
2000
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 143 publications
(182 citation statements)
references
References 14 publications
(24 reference statements)
16
161
3
2
Order By: Relevance
“…For women not taking oral contraceptives, however, the quadriceps were stronger, more fatiguable and had a longer relaxation time at mid-cycle (day 12-18). Phillips et al (1996) reported a higher adductor pollicis strength during the follicular phase than during the luteal phase, with a rapid decrease in strength around ovulation. They suggested that oestrogen has a strengthening action on skeletal muscle, although the underlying mechanism is not clear.…”
mentioning
confidence: 97%
“…For women not taking oral contraceptives, however, the quadriceps were stronger, more fatiguable and had a longer relaxation time at mid-cycle (day 12-18). Phillips et al (1996) reported a higher adductor pollicis strength during the follicular phase than during the luteal phase, with a rapid decrease in strength around ovulation. They suggested that oestrogen has a strengthening action on skeletal muscle, although the underlying mechanism is not clear.…”
mentioning
confidence: 97%
“…N et al 34 assessed the response of athletes using various preparations of OCs (n = 13) and athletes not using hormonal contraception (n = 18) to 12 weeks of resistance training. Strength was improved in both groups, with no apparent di erences between groups, although this study did not control for menstrual cycle phase when measuring strength in the control group, which has been shown to a ect force production 36 . In contrast, L et al 35 found that non-OC users (n = 39) gained signi cantly more muscle mass (+3.5%) than OC users (n = 34; +2.1%) following a 10 week training programme.…”
Section: Is There a Relationship Between Hormonal Contraceptives And mentioning
confidence: 85%
“…During the eighties and nineties there was much debate and controversy about the e ects of ovarian hormones on muscle strength in females [1][2][3][4][5] . Researchers used various models of reproductive functioning to investigate this relationship including; the menstrual cycle 6 , the menopause 7 , in vitro fertilisation (IVF) treatment 8 , pregnancy 9 , oral contraceptives 10 (OC's) and hormone replacement therapies 11 (HRT's).…”
Section: Introductionmentioning
confidence: 99%
“…Since then, several authors have linked cyclical changes in muscle strength, in eumenorrheic females, with uctuations in ovarian hormone levels across the menstrual cycle 3,4,10,[16][17] . However, there is also substantial evidence to the contrary 1,5,[18][19][20] .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation